Analisis dan Evaluasi Peraturan Daerah No. 5 Tahun 2011 tentang Pelarangan Perjudian di Kabupaten Kolaka Utara: Analisis dan evaluasi peraturan daerah - Wirahana, Aden Wirahana Putra (Faculty of Law, University of Muhammadiyaha Surabaya, 2024)
Local regulations are a form of authorization for city governments to fulfill regional autonomy and responsibility. The aim is to provide assistance and adjustments to special situations in an area or as additional explanations regarding more detailed regulations. In the context of North Kolaka Regional Regulation no. 5 of 2011 concerning the Prohibition of Gambling, there is ambiguity and a need for revision. Therefore, the problem formulation in this research is: 1.) What is the Urgency of Analysis and Evaluation of the Regional Regulation? 2.) How is the Regional Regulation analyzed and evaluated? This research uses a normative legal method with a state approach which concludes that: 1) Analysis and evaluation of regional regulations is important to provide input for policy updates or improved implementation that is more effective. 2) Immediate revision of Article 1 Paragraph 5, Article 3 Point b, Article 7 Paragraphs 1 and 2, and Articles 6 and 8 is required